Analysis of footwork diagrams from Libro de las grandezas de la espada - Darío Sánchez García (Acta Periodica Duellatorum)
The goal of this analysis is to search for a plausible explanation of the rules followed by Pacheco in Libro de las grandezas de la espada to construct the footwork theory explained in it. For this purpose, we are going to geometrically analyse the diagrams presented in the treatise, we are studying it in the order the concepts are explained in the treatise: a presentation of a rigid explanation of the footwork and an apparently low-consistent application of it through the footwork diagrams. Thus, we will compile the data presenting some hypotheses that appear along the way until we can rearrange it to see the pattern that gives us a plausible construction rule for the footwork diagrams. In order to obtain a rule consistent with later Verdadera Destreza treatises and theory, and therefore more plausible as all of them claimed to follow Pacheco’s teachings, we will present a brief analysis of several treatises Common Circle descriptions to see how the conclusions reached match with them. Finally, we are proposing a rule set that Pacheco may have used and an application of it to reconstruct some diagrams of the treatise.